Evaluation of functional maturity for a network information service - design and case analysis. (19th November 2021) - Rawajbeh, Mohammad Al; Sayenko, Vladimir I.; Alhadid, Issam Hamad; Al-Turjman, Fadi; Ramasamy, Lakshmana Kumar
The current study discusses methodological issues for monitoring process to control the state of developing information system. The main goal of this evolutionary process is to achieve the optimal value for some criteria. The proposed approach is considered as a conception for the evolution of properties for system (object) at the planning phase. The study has proposed the evolution conception of system properties for planning (development) phase, concept of improving the system properties, the indicators of the functional maturity, and the technique of evaluation of functional maturity. The planning phase, the quality indicators named 'functional maturity' is a concept of the evaluation of functional maturity in which estimates of the functional maturity indicators and a technique for functional maturity evaluation monitoring conception are done. The implementation of this technique has developed a tier-based procedure. The results have demonstrated that network planning should follow integrated work practices along with the implementations of solid system design.